Economic analysis of pharmacist-administered influenza vaccines in Ontario, Canada - O'Reilly DJ; Blackhouse G; Burns S; Bowen JM; Burke N; Mehltretter J; Waite NM; Houle SKD (Dove Medical Press, 2018)
Daria J O’Reilly,1,2 Gord Blackhouse,1,2 Sheri Burns,2 James M Bowen,1,2 Natasha Burke,1,2 Jeff Mehltretter,3 Nancy M Waite,4 Sherilyn KD Houle4 1Department of Health Research Methods, Evidence, and Impact, Faculty of Health Sciences, McMaster University, Hamilton, ON, Canada; 2Programs for Assessment of Technology in Health (PATH), The Research Institute of St. Joe’s Hamilton, Hamilton, ON, Canada; 3Neighbourhood Pharmacy Association of Canada, Toronto, ON, Canada; 4School of Pharmacy, Faculty of Science, University of Waterloo, Waterloo, ON, Canada Objective: The aim of this study was to evaluate the impact of pharmacist administration of influenza vaccine in Ontario on: 1) vaccination-associated costs related to the number of people vaccinated; 2) annual influenza-related outcomes and costs; and 3) change in productivity costs. Methods: Using available data for Ontario, the total number of vaccinations given by providers in the 2011/12 influenza season (pre) was compared to the 2013/14 influenza season (post). Vaccine costs and provider fees for administration were assigned for both periods. An economic model was created to estimate the impact of the change in influenza vaccination volume on influenza-related outcomes and on the health care costs associated with treating influenza-related outcomes. Productivity costs due to both time off work due to getting vaccinated and influenza illness were considered. One-way sensitivity analysis was used to assess parameter uncertainty. Results: The number of vaccinations received by Ontarians increased by 448,000 (3% of the population), with pharmacists vaccinating approximately 765,000 people/year. The increased cost to the Ontario Ministry of Health and Long-term Care was $6.3 million, while the money saved due to reduced influenza-related outcome costs was $763,158. Productivity losses were reduced by $4.5 million and $3.4 million for the time invested to get vaccinated and time off work due to influenza illness, respectively. Conclusion: After two influenza seasons, following the introduction of pharmacist-administered influenza vaccinations, there was a net immunization increase of almost 450,000, which potentially saved $2.3 million in direct health care costs and lost productivity in the province. Keywords: universal influenza vaccination, costs, pharmacist, productivity, immunization